2014
DOI: 10.1007/s00109-014-1129-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: master regulators of drug resistance, stemness, and metastasis

Abstract: MicroRNAs (miRNAs) are 20-22 nucleotides long small non-coding RNAs that regulate gene expression post-transcriptionally. Last decade has witnessed emerging evidences of active roles of miRNAs in tumor development, progression, metastasis, and drug resistance. Many factors contribute to their dysregulation in cancer, such as chromosomal aberrations, differential methylation of their own or host genes' promoters and alterations in miRNA biogenesis pathways. miRNAs have been shown to act as tumor suppressors or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 180 publications
(153 reference statements)
0
43
0
Order By: Relevance
“…m iR NAs a re deregulated in numerous human cancers (23,24). Previous studies have demonstrated that miRNAs are reliable and cost-effective biomarkers that can be utilized in the diagnosis and assessment of the progression, therapeutic response and prognosis of a wide spectrum of malignant tumors, including esophageal cancer (7,(25)(26)(27). A better understanding of the miRNAs associated with particular cancers would provide valuable insights for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…m iR NAs a re deregulated in numerous human cancers (23,24). Previous studies have demonstrated that miRNAs are reliable and cost-effective biomarkers that can be utilized in the diagnosis and assessment of the progression, therapeutic response and prognosis of a wide spectrum of malignant tumors, including esophageal cancer (7,(25)(26)(27). A better understanding of the miRNAs associated with particular cancers would provide valuable insights for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, involvement of miRNAs in combined regulation of drug resistance and EMT is evident [74]. Likewise, miR-200c, a negative regulator of EMT, has shown great potential to overcome both chemotherapy and targeted therapy resistance through reversing the EMT process or promoting epithelial-like state (Fig.…”
Section: Mir-200c At the Intersection Of Emt And Drug Resistancementioning
confidence: 99%
“…MiRNAs regulate a wide array of cell functions such as proliferation, differentiation, migration, and apoptosis, and are implicated in various pathological conditions including tumorigenesis [4-7]. Accumulating evidence also suggests that dysregulation of specific miRNAs may be involved in the acquisition of drug resistance of a number of cancers, particularly lung cancer [8, 9]. Identifying miRNAs implicated in NSCLC and understanding the mechanisms by which they regulate NSCLC tumorigenesis and/or drug resistance is of critical importance in seeking to improve NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%